A-Z of corporate environmental management - Sadgrove, Kit (Earthscan, 2005)
Is aluminium bad for you? What is an Environment Management System? Is there an effective substitute for Chlorine Bleach? The A - Z of Corporate Environmental Management provides answers to these and many other questions, and is an invaluable guide to managing a company's environmental impact. This practical directory assesses hundreds of products in common use, from aerosols to zinc, via formaldehyde and phosphates. Using an easy-to-understand format it: explains each product's use, its benefits and its environmental risks; recommends safer alternative choices where available; explains issues.